2015
DOI: 10.1007/jhep11(2015)034
|View full text |Cite
|
Sign up to set email alerts
|

Non-zero θ 13 and δ CP in a neutrino mass model with A4 symmetry

Abstract: In this paper, we consider a neutrino mass model based on A 4 symmetry. The spontaneous symmetry breaking in this model is chosen to obtain tribimaximal mixing in the neutrino sector. We introduce Z 2 × Z 2 invariant perturbations in this model which can give rise to acceptable values of θ 13 and δ CP . Perturbation in the charged lepton sector alone can lead to viable values of θ 13 , but cannot generate δ CP . Perturbation in the neutrino sector alone can lead to acceptable θ 13 and maximal CP violation. By … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Here again, radiative corrections or other explicit A 4 breaking terms can lead to a phenomenologically viable form of the PMNS matrix with non-zero θ 13 and δ C P . For example, in ref [11], A 4 symmetry was softly broken by unequal Majorana masses for ν i R . A simple adjustment of these masses leads to the correct value of θ 13 and maximal CP violation.…”
Section: Yukawa Lagrangian and Charged Fermions In Mass Eigenbasismentioning
confidence: 99%
See 1 more Smart Citation
“…Here again, radiative corrections or other explicit A 4 breaking terms can lead to a phenomenologically viable form of the PMNS matrix with non-zero θ 13 and δ C P . For example, in ref [11], A 4 symmetry was softly broken by unequal Majorana masses for ν i R . A simple adjustment of these masses leads to the correct value of θ 13 and maximal CP violation.…”
Section: Yukawa Lagrangian and Charged Fermions In Mass Eigenbasismentioning
confidence: 99%
“…In Ref. [11], it was shown that the introduction of a small perturbation in the Majorana mass matrix of the heavy right-chiral neutrinos in this model, can lead to both a realistic value of sin 2 θ 13 ≈ 0.02 and maximal CP violation.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2). The physical reason may be caused by the Majorana-Dirac confusion theorem [3] because the neutrino masses are not important factor for the neutrino oscillations in these cases. Such an oscillating behavior of Poincaré radius demonstrates that the CP violation enhances the neutrino oscillations just like the matter potential.…”
Section: )mentioning
confidence: 99%
“…Hence the texture I with two degenerate and one massless neutrino can follow in any ∆(12k 2 ). The smallest such group is ∆(12) = A 4 which is one of the most studied flavour symmetry from other points of view [43][44][45][46][47][48][49][50][51][52].…”
Section: Jhep11(2015)186mentioning
confidence: 99%
“…We now present an explicit realization of flavour antisymmetric neutrino mass matrix using A 4 as an example. A 4 has been extensively used for several different purposes, for obtaining degenerate neutrinos [43,44], to realize tri-bimaximal mixing [45,48] for obtaining maximal CP phase δ [46,47,49,51,52] or to obtain texture zeros [50] in the leptonic mass matrices. As we discuss here, it also provides a viable alternative to get a massless and two quasi degenerate neutrinos with correct mixing pattern.…”
Section: Jhep11(2015)186mentioning
confidence: 99%